GOSPEL TEXT IN SCIENCE FICTION NOVELETTES BY V. P. KRAPIVIN (THE CYCLE "IN THE HEART OF THE GREAT CRYSTAL") - Velikanova E. A. (Problemy Istoričeskoj Poètiki, 2011)
The article analyses evangelical motives and images in a cycle of science fiction stories In the heart of the Great Crystal by Vladislav Krapivin. The reference to the evangelical text and connection to folklore and literary elements create the modern moral maintenance of books of the writer addressed to the teenage reader.